2004
DOI: 10.1179/136217104225021634
|View full text |Cite
|
Sign up to set email alerts
|

Integrated fracture mechanics approach to analyse fatigue behaviour of welded joints

Abstract: Current fracture mechanics methods for fatigue assessment, including those that consider thresholds for crack propagation, are based on long crack behaviour. The present work is concerned with an attempt to predict the fatigue strength of welded joints using a fracture mechanics approach that takes into account the fatigue behaviour of short cracks. The methodology estimates the fatigue crack propagation rate as a function of the difference between the applied driving force and the material threshold for crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Previous works have been done by using the proposed method in order to analyze the influence of different weld geometry parameters on the fatigue resistance of welded joints, like plate thickness, reinforcement angle, weld toe geometry, defect sizes and undercuts [7][8][9][10]. Results showed that the method allows understanding the influence of the different mechanical, geometrical and microstructural parameters on the definition of the fatigue resistance of the joint.…”
Section: Previous Analysis and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous works have been done by using the proposed method in order to analyze the influence of different weld geometry parameters on the fatigue resistance of welded joints, like plate thickness, reinforcement angle, weld toe geometry, defect sizes and undercuts [7][8][9][10]. Results showed that the method allows understanding the influence of the different mechanical, geometrical and microstructural parameters on the definition of the fatigue resistance of the joint.…”
Section: Previous Analysis and Resultsmentioning
confidence: 99%
“…Finally, it is important to say that although fixed global geometry and loading condition were used in the analysis of the influence of undercuts, the proposed method can scientifically explain the effect and relevance of most of the mechanical and geometrical parameters, as was shown in references [7], [8], [9] and [10].…”
Section: Previous Analysis and Resultsmentioning
confidence: 99%
See 3 more Smart Citations